Clinical measurement and evaluation of vertical dimension of face - Dipoyono, Haryo Mustiko; Samsudin, Ab. Rani; Sugiatno, Erwan; Omar, Norshamsuria (2002)
The vertical dimension(VD) is very important because it refers to the vertical distance between the maxilla and mandible with the teeth in occlusion. In full denture contruction specialty in edentulous cases, it is very difficult accurately to reproduce the vertical dimension of the former dentate condition. The objectives of the research were to compare and evaluate three methods of determining VD:(i)the Simplified Method of Hayakawa; (ii) the indicator Procedure of Hayakawa and (iii) the Dipoyono and Sugiatno Method. The number of subjects used to test method was 30. In Addition to the measurements that were used to determine VD, additional information was obtained from the subjects about facial form and the palm of the hand. Mean deformation (in mm) were 57.3267 (The Simplified Method of Hayakawa) ; 56.98027 (The Indicator Procedure of Hayakawa) and 61.7167 (The Dipoyono and Sugiatno Method). This difference was significant (p<0.01) as tested by pair t- test. It was found that the methods of Hayakawa were very complicated to use but the Dipoyono and Sugiatno is simple and quick to use.